2012
DOI: 10.1080/1533256x.2012.646588
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work-Related Factors on Soldiers' Treatment: Providers' Perspectives

Abstract: Military settings present a unique context that can affect the continuity of care for substance abuse and other issues. We examined the impact of military work-related factors (increased work tempo, deployment, and permanent change of station) on treatment disruption for substance abuse and family violence among Army soldiers from the perspective of substance abuse treatment providers and clinical social workers. Among the 264 respondents, nearly 90% of providers reported that work-related factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It is surprising then that within such a large organization such as the CAF, that features a complex, demanding and stressful career that is descriptive of the CAF members' roles and responsibilities, that there is so little research available that explores the role of social work and social services with and for the CAF. Indeed, while there are studies available that relate to the military in general, most are American-based in nature, focusing predominantly on: the impact of deployment and warrelated stress on the mental health of service members (Asbury & Martin, 2012;Beder, Coe, & Sommer, 2011;Castro, 2009;Hammelman, 1995), mental health concerns and barriers to seeking treatment (Bennett, Crabtree, Schafer, & Britt, 2011;Castro et al, 2004;Clinton-Sherrod, Gibbs, Walters, Martin, & Johnson, 2012;Drapalski, Milford, Goldberg, Brown, & Dixon, 2008;Elbogen et al, 2013;Hoge, Auchterlonie, & Milliken, 2006;Kim, Britt, Klocko, & Riviere, 2011;Vogt, 2011), effects of job-related stress (Bray, Camlin, Fairbank, Dunteman, & Wheeless, 2001), and military culture and social work with veterans (Wheeler & Bragin, 2007).…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…It is surprising then that within such a large organization such as the CAF, that features a complex, demanding and stressful career that is descriptive of the CAF members' roles and responsibilities, that there is so little research available that explores the role of social work and social services with and for the CAF. Indeed, while there are studies available that relate to the military in general, most are American-based in nature, focusing predominantly on: the impact of deployment and warrelated stress on the mental health of service members (Asbury & Martin, 2012;Beder, Coe, & Sommer, 2011;Castro, 2009;Hammelman, 1995), mental health concerns and barriers to seeking treatment (Bennett, Crabtree, Schafer, & Britt, 2011;Castro et al, 2004;Clinton-Sherrod, Gibbs, Walters, Martin, & Johnson, 2012;Drapalski, Milford, Goldberg, Brown, & Dixon, 2008;Elbogen et al, 2013;Hoge, Auchterlonie, & Milliken, 2006;Kim, Britt, Klocko, & Riviere, 2011;Vogt, 2011), effects of job-related stress (Bray, Camlin, Fairbank, Dunteman, & Wheeless, 2001), and military culture and social work with veterans (Wheeler & Bragin, 2007).…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 99%
“…From a provider's perspective, it has been reported that work-related issues in the military affects not only care seeking, but treatment continuity as well. The study by Clinton-Sherrod et al (2012) found that work-related factors (such as increased work tempo, deployment, and permanent change of station) not only have an impact on treatment for substance use and family violence but "other barriers to treatment such as resource issues, coordination of care, command support of treatment, and the participation of soldiers and families in treatment" (p. 84) impact treatment seeking and continuity as well. These additional barriers and factors affecting treatment, however, have yet to be explored.…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations